Donations help ease the burden of UMP landscaping workers - Nor Salwana, Mohammad Idris (2021)
PEKAN, 16 July 2021 - The existence of the Universiti Malaysia Pahang (UMP) campus close to the local community in Kuala Pahang benefits the community when 67 people have the opportunity to serve as professional workers for the landscape at this university.